2011
DOI: 10.1002/ibd.21597
|View full text |Cite
|
Sign up to set email alerts
|

Heat-killed body of lactobacillus brevis SBC8803 ameliorates intestinal injury in a murine model of colitis by enhancing the intestinal barrier function

Abstract: The administration of heat-killed L. brevis SBC8803 helps to successfully maintain intestinal homeostasis, while also curing intestinal inflammation. A therapeutic strategy using heat-killed bacteria is expected to be beneficial for human health even in conditions unsuitable for live probiotics because the heat-killed body is able to exhibit its effects without the requirement of colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 65 publications
(61 reference statements)
3
69
0
Order By: Relevance
“…p38 activity is increased significantly in tissues from IBD patients and in mouse models of colitis [83,84,88] , in which inhibition of p38 lowers KC (IL-8) and IL-6 production. A similar result was reported that heatkilled Lactobacillus brevis phosphorylates p38 kinase to regulate the expression of proinflammatory cytokines such as TNF-α, and to improve intestinal integrity [89] . JNK1/2 kinase activity was enhanced in IBD inflamed tissue and blockage of JNK1/2 in experimental colitis reduced the production of proinflammatory cytokines [84,90,91] .…”
Section: Of Ibdsupporting
confidence: 74%
“…p38 activity is increased significantly in tissues from IBD patients and in mouse models of colitis [83,84,88] , in which inhibition of p38 lowers KC (IL-8) and IL-6 production. A similar result was reported that heatkilled Lactobacillus brevis phosphorylates p38 kinase to regulate the expression of proinflammatory cytokines such as TNF-α, and to improve intestinal integrity [89] . JNK1/2 kinase activity was enhanced in IBD inflamed tissue and blockage of JNK1/2 in experimental colitis reduced the production of proinflammatory cytokines [84,90,91] .…”
Section: Of Ibdsupporting
confidence: 74%
“…Indeed, it has been shown that several probiotics, such as Lactobacillus, Bifidobacterium, E. coli Nissle and Clostridium, ameliorate intestinal injury caused by acute inflammation, that is often observed in patients with antibiotic-induced colitis 9,10 , necrotizing colitis 11,12 and IBD [13][14][15][16][17][18] . We recently isolated an effective molecule, competence and sporulation factor (CSF), from the conditioned media of the probiotic Bacillus subtilis, and demonstrated that this molecule enhanced the intestinal barrier function and improved the intestinal injury in an acute enteritis 8 model 19,20 . We subsequently showed that the administration of heat-killed Lactobacillus brevis SBL88 (L. brevis SBL88) helps to maintain intestinal homeostasis and improves intestinal inflammation 21 . Furthermore, the conditioned media from L. brevis SBL88 was repeatedly separated by ammonium sulfate precipitation, DEAE anion exchange chromatography and gel filtration, and a fraction that could induce the expression of cytoprotective heat-shock protein (Hsp) 27 in Caco2/bbe cells was isolated.…”
mentioning
confidence: 99%
“…This finding is substantiated further by an in vitro study, indicating that inhibition of p38 using the natural IL-1 receptor antagonist, in a colonocyte cell line, leads to reduced IL-6 and -8 production, and an in vivo study using a murine model of IBD, where inhibition of p38 reduced significantly cytokine mRNA and NFκB activation (Garat et al, 2003;Hollenbach et al, 2004). However, Heat-killed L. brevis SBC8803 induced Hsps, phosphorylated p38 MAPK, regulated the expression of tumor necrosis factor alpha (TNF-), interleukin (IL)-1 and IL-12, and improved the barrier function of intestinal epithelia under oxidant stress (Ueno et al, 2011). There are three JNK isoforms, JNK1, 2 and 3, of which there are 10 splice forms in total.…”
Section: Mitogen Activated Protein Kinases (Mapk)mentioning
confidence: 99%